Mutações constitucionais na modernidade periférica: os efeitos das mudanças simbólicas da constituição - Silva, Heitor Nogueira da (2019)
The present work intends to highlight the constitutional mutations in the context of the problems inherent to the peripheral countries, identifying whether, under this circumstance, the performance of the constitutional courts, mainly from the Federal Supreme Court, results in effectiveness or symbolism. For this purpose, the dissertation assignment is going to accomplish the bibliographical research, mainly from the writings drafted by Marcelo Neves related to the subject of this dissertation, as well as authors who either develop or critically reflect Neves’s concept, aiming at a qualitative analysis. In the first moment, the theoretical assumptions are shown for a theoretical-systemic approach to the symbolic changes of the Constitution, building the contours of the conceptions such as Constitution, constitutionalism and constitutional norms in modernity, to subsequently characterize the symbolic constitutionalization as an innate obstacle for countries in peripheral modernity. During the second chapter, it is sought to discuss the rise and development of the constitutional mutation theory to the debate about the limits of the constitucional mutation as a guarantee of the Constitution’s normative force. In the third moment, it is aimed to check if the actions done by the Federal Supreme Court, in cases of constitutional mutation, are emerged by the prevalence of the political-ideological meaning to the detriment of the legal-normative concretion, setting up in symbolism or effectiveness. Afterward, in the final chapter, it is seen the effects of the symbolic changes of the Constitution, allusive to the Brazilian case, and the strong tendency of symbolic "judicialization" as a new dimension of symbolic constitutionalization, a scenario in which is identified the semantic degradation of the constitutional text in the process of interpretation / application of the Constitution and the intensification of relations of over-integration and sub-integration in the achievement of fundamental rights, duties and guarantees. Finally, as a form to illustrate the symbolic nature of the Federal Supreme Court's actions in mutations, it discusses the symbolism of the unconstitutional mutation on the presumption of innocence through the recent Supreme Court turnarounds.